Clinical Research: Auditory Stimulation in the Disorders of Consciousness - Zhu, Jiajie; Yan, Yifan; Zhou, Wei; Lin, Yajun; Shen, Zheying; Mou, Xuanting; Ren, Yan; Hu, Xiaohua; Di, Haibo (Frontiers in Human Neuroscience, 2019)
Due to the complex situation of disorder of consciousness (DOC) patients, the assessment of conscious states of these patients has become a huge challenge for a long time (Laureys et al., 2010). At present, the main clinical diagnostic method to assess the conscious state of a DOC patient is the use of a relevant behavior scale like the Coma Recovery Scale-Revised (CRS-R). In this article, we will focus on auditory stimulation and select some representative auditory stimulus, like calling names and music stimulation, to discuss the function and application of the auditory stimulus in patients with DOC and provide guidance for future research.